Avaliação da confiabilidade de estruturas existentes: influência da resistência à compressão do concreto - Billy Lukusa Badimuena (2017)
In developed societies, a significant proportion of existing structures have already exceeded the project lifetime. Logically, these structures should be evaluated to determine their current security conditions. In recent years, in North America, resources spent on repairing andretrofitting existing structures were greater than those invested in building the new ones. Nowadays, the evaluation of existing structures with a view to their adaptation to the proposed use, rehabilitation or even demolition is a challenging and more relevant process. Design codes for new structures deal with uncertainties associated with design and construction. On the other hand, much of what was initially uncertain, ceases to be so after the work is completed. A conceptual and philosophical difference between the design of new structures and theassessment of existing ones is indispensable to delimit both activities. Thus, there are normative documents being developed exclusively for the assessment of existing structures. Relevant contributions from these documents include requirements for evaluation methods and procedures as well as intervention project techniques. One of the challenges for the elaboration of fib MC 2020 (CEB-FIP) is to incorporate provisions regarding the evaluation of existing structures. However, in Brazil, the problem of evaluation, rehabilitation and repairs of existing structures is still not seen from the perspective of exclusivity. Design rules for new structures are usually employed for assessing the existing structures. Given the randomness in determining the key quantities (dimensions of elements, in situ resistance, plumb, etc.) of existing structures, their normative recommendations should be elaborated at least consistent with the semiprobabilistic methods (LRFD). An important issue is the definition of the target reliability index to be used in the calibration. This dissertation presents a discussion about the assessment of the safety of existing structures from the point of view of the practice of the evaluation exercise, the calibration of design codes, especially the definition of the objective to be achieved. Finally, reliability indexes associated with existing structures were evaluated by means of short columns under centered compression. It has been possible to determine the influence of in situ compressive strength on the reliability levels obtained, highlighting the impact of its variability on the reliability